Integrating Vietnam’s Living Heritage into STEM Education: The Case of Vietnamese Conical Hat - Dao, Quyen; Do Hoang, Son; Tran Thi Thanh, Tam; Ngo Ngoc, Thuy (SEAMEO QITEP in Science, 2025)
This study presents an innovative integration of STEM education with the preservation of Vietnam’s living heritage through the traditional craft of the Vietnamese conical hat at Gia Thanh Secondary School. The project aims to enhance student engagement in STEM by embedding the conical hat’s cultural production process into Mathematics, Science, and Engineering lessons. Over 200 students participated in hands-on activities by applying geometric principles to design the conical hat, exploring material science using natural materials, and learning engineering concepts through traditional crafting methods. Overall, 85% of students reported that their interests had increased in STEM subjects, as measured by performance in geometry (95% success) and material science (80% engagement). Furthermore, the initiative connected students with local artisans, fostering cultural pride and raising awareness of the economic and cultural importance of the conical hat. By integrating heritage preservation with STEM education, this project demonstrates a replicable model for enriching STEM learning while maintaining local cultural traditions.